Effect of different nutrients on sweet pepper (Capsicum annuum) in mid hills of Himachal Pradesh - SHARMA, ARCHANA; SHARMA, JAGJEET CHAND; GAUTAM, KRISHAN LAL (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted during rainy (kharif) season of 2020 and 2021 to study the influence assessment of different nutrients in sweet pepper (Capsicum annuum var. Grossum L.) Experiment comprised of 9 treatments laid in randomized block design (RBD) tested against absolute control. Two year pooled data analysis revealed that, application of 150% NPK + FYM produced maximum number of fruits (11.62), fruit length (7.37 cm), fruit width (6.76 cm), average fruit weight (73.0 g), HI (31.60 %), yield (314.3 q/ha) and earned maximum net returns (₹462215.8). Treatment T9 (150% NPK + FYM) also recorded maximum plant nutrient contents and their uptake, and found to be statistically at par with T8 (100% NPK + FYM) which also recorded higher benefit-cost ratio. Application of 100% NPK produced 239.2 q/ha capsicum and gave net returns of ₹373618.8 and 3.56 benefit cost (B:C) ratio. Application of 100% NPK + FYM recorded 289.6 q/ha capsicum yield and net returns of ₹435785.4 with B:C of 3.04 and proved as the best treatment for enhancing yield and economics of capsicum under mid hills of Himachal Pradesh. Therefore, the recommended practice, i.e. Application of 100% NPK (100: 76: 54 kg/ha) + FYM (250 q/ ha) is the best alternative of NPK inorganic fertilizers and best nutrient management practice to exploit the better eco-friendly economic capsicum yield.